Empowerment Through Integrated Marketing Communication (IMC) Assistance and Training to Improve the Economy in Orphanage Communities - Fatimah; Putri, Ananda; Setyadji, Veronika (Jurnal Pengabdian Masyarakat, 2025)
Purpose: Since the Covid-19 pandemic, the Siti Khadijah Al-Kubra Orphanage has initiated self-reliance in its operations, particularly through small businesses. This effort was driven by the decrease in donors since the Covid-19 pandemic, which affected the economy in the orphanage's surrounding community. The business ventures include refillable water and laundry services. Method: The methods used in this service include training, technology application, technology assistance, and sustainability. Practical Application: The goal of this community service is to provide training and guidance on integrated marketing communication within the orphanage environment to improve the economy. This initiative is carried out in collaboration with the Siti Khadijah Al-Kubra Orphanage. Conclusion: This community service activity resulted in approximately 90% understanding among participants regarding integrated marketing communication, small business management, and the application of technology to support business sustainability.